Study of Ratio fission width to total width for fission materials bombarded by monoenergitic neutrons (Baghdad Science Journal, 2008)
This study aims to know the way of the ratio fission width to total width for compound nuclei of fission materials , when it had been bombarded by monoenergetic neutrons as a function of nuclear radius and ranges ( 1-10) *10-13 cm , and it concluded the mathematical equations that can be used for this way of the study . Also we concluded the empirical relations by fitting method in which the ratio fission width to the total width for monoenergitic neutrons for various fission nucleuses, for Uranium-238 and Thorium-232 respectively.